Human electronegative LDL induces mitochondrial dysfunction and premature senescence of vascular cells in vivo - (:unkn) unknown (WILEY, 2018)
Dysregulation of plasma lipids is associated with age-related cardiovascular diseases. L5, the most electronegative subfraction of chromatographically resolved low-density lipoprotein (LDL), induces endothelial dysfunction, whereas the least electronegative subfraction, L1, does not. In this study, we examined the effects of L5 on endothelial senescence and its underlying mechanisms. C57B6/J mice were intravenously injected with L5 or L1 (2 mg kg(-1) day(-1)) from human plasma. After 4weeks, nuclear gamma H2AX deposition and senescence-associated beta-galactosidase staining indicative of DNA damage and premature senescence, respectively, were increased in the aortic endothelium of L5-treated but not L1-treated mice. Similar to that, in Syrian hamsters with elevated serum L5 levels induced by a high-fat diet, nuclear gamma H2AX deposition and senescence-associated beta-galactosidase staining were increased in the aortic endothelium. This phenomenon was blocked in the presence of N-acetyl-cysteine (free-radical scavenger) or caffeine (ATM blocker), as well as in lectin-like oxidized LDL receptor-1 (LOX-1) knockout mice. In cultured human aortic endothelial cells, L5 augmented mitochondrial oxygen consumption and mitochondrial free-radical production, which led to ATM activation, nuclear gamma H2AX deposition, Chk2 phosphorylation, and TP53 stabilization. L5 also decreased human telomerase reverse transcriptase (hTERT) protein levels and activity. Pharmacologic or genetic manipulation of the reactive oxygen species (ROS)/ATM/Chk2/TP53 pathway efficiently blocked L5-induced endothelial senescence. In conclusion, L5 may promote mitochondrial free-radical production and activate the DNA damage response to induce premature vascular endothelial senescence that leads to atherosclerosis. Novel therapeutic strategies that target L5-induced endothelial senescence may be used to prevent and treat atherosclerotic vascular disease.
Keywords: atherosclerosis; DNA damage response; electronegative lipoproteins; mitochondria; premature senescence; telomerase; LOW-DENSITY-LIPOPROTEIN; DNA-DAMAGE; OXIDATIVE STRESS; HISTONE H2AX; ATHEROSCLEROSIS; MECHANISMS; APOPTOSIS; TELOMERASE; ARTERIAL; LOX-1